A clastic-evaporitic deposit from the Cretaceous of northeastern Mexico: La Mula-La Virgen transition. (December 2017) - Gutierrez-Alejandro, Alejandra G.; Chacon-Baca, Elizabeth; Rosales-Domínguez, Carmen; Ramírez-Peña, César Francisco; Girón, Patricia; Grajales-Nishimura, José Manuel
Abstract: Units from La Mula and La Virgen formations outcrop in central Coahuila in northeastern Mexico. During the Early Cretaceous this sedimentary succession was deposited between the Coahuila and the Tamaulipas blocks as a transitional ramp succession that later became the Sabinas Basin. For years, the lack of fossils in La Virgen Formation has prevented a precise age resolution. This work provides new biostratigraphic data from Potrero de Menchaca, a representative locality that records a siliciclastic-carbonate transition from the clastic La Mula Formation and the evaporites from La Virgen Formation. The microfacies association indicates the presence of foraminiferan representatives of Choffatella decipiens and Charentia sp. in close association with the rare green alga Thaumotoporella parvovesiculifera, a few mollusk bioclasts and other algal fragments that gradually increase in size as the evaporitic succession become more frequent. In addition to the microfossils reported, a significant contribution of this work includes a preliminary geochemical analysis from the preceding green shales from La Mula Formation, which are reported from the first time for this locality and holds high potential for provenance studies. Highlights: Choffatella decipiens, Charentia sp. and Thaumotoporella parvovesiculifera with Tethyan counterparts are reported within a Cretaceous evaporitic succession in northeastern Mexico. Preservation of marine microfossils from La Virgen Formation associated with mollusk shells might be indicative of basal transgressive events within along a ramp. The petrographic and chemical description of siliciclastic horizons from La Mula Formation with potential utility in provenance studies are provided for the first time for Potrero de Menchaca, Coahuila, Mexico.